2023
DOI: 10.1002/tpg2.20326
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of UK bread baking quality: Trends in wheat quality traits over 50 years of breeding and potential for future application of genomic‐assisted selection

Abstract: Improved selection of wheat varieties with high end‐use quality contributes to sustainable food systems by ensuring productive crops are suitable for human consumption end‐uses. Here, we investigated the genetic control and genomic prediction of milling and baking quality traits in a panel of 379 historic and elite, high‐quality UK bread wheat (Triticum eastivum L.) varieties and breeding lines. Analysis of the panel showed that genetic diversity has not declined over recent decades of selective breeding while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 125 publications
0
1
0
2
Order By: Relevance
“…Voorgaande onderzoeken geven aan dat enkel naar eiwitgehalte kijken beperktere informatie over bakkwaliteit geeft in vergelijking met het kijken naar de gehele eiwitsamenstelling. Een beperking van een voorgaande studie (Thanhaeuser et al, 2014) (Fradgley et al, 2023;Laidig et al, 2017Laidig et al, , 2022. Het is daarom belangrijk…”
Section: Eiwitsamenstellingunclassified
See 1 more Smart Citation
“…Voorgaande onderzoeken geven aan dat enkel naar eiwitgehalte kijken beperktere informatie over bakkwaliteit geeft in vergelijking met het kijken naar de gehele eiwitsamenstelling. Een beperking van een voorgaande studie (Thanhaeuser et al, 2014) (Fradgley et al, 2023;Laidig et al, 2017Laidig et al, , 2022. Het is daarom belangrijk…”
Section: Eiwitsamenstellingunclassified
“…Het is van belang te beseffen dat rassenkeuze en teeltmaatregelen maar tot een bepaalde hoogte kunnen bijdragen aan het verbeteren van broodvolume of een andere eigenschap. Uit verscheidene studies is naar voren gekomen dat er een verschil zit tussen de invloed van rassenkeuze en teeltmaatregelen op bijvoorbeeld eiwitgehalte of broodvolume (Fradgley et al, 2023;Laidig et al, 2017Laidig et al, , 2022. Zo wordt variatie in het eiwitgehalte voor 21 tot 35% verklaard door het ras terwijl de rest van de variatie wordt verklaard door management en omgeving (bemesting, gewasbescherming, weer etc.).…”
Section: 3unclassified
“…While decades of primary emphasis on grain yield improvement have delivered increased gains worldwide [22][23][24], the trends are mixed for quality traits [22,25]. Grain protein content has declined [23,26,27], probably due to the strong trade-off with grain yield, but positive genetic gains were found for dough strength related parameters (mixograph mixing time, torque, alveograph) and the overall quality of bread has increased [27,28]. The wholegrain free amino acid content is not normally targeted in breeding programs, but despite this, Anjum et al [29] reported that newly released wheat cultivars are nutritionally more superior than the old wheat cultivars, especially in the percentages of essential amino acids, particularly lysine.…”
Section: Introductionmentioning
confidence: 99%